Malaria Mortality in Brazil: Age–Period–Cohort Effects, Sociodemographic Factors, and Sustainable Development Indicators - Mariusa Fernandes de Farias; Eric Renato Lima Figueiredo; Raimundo Nelson Souza da Silva; Deizyane dos Reis Galhardo; Cleide Laranjeira da Silva; Evelyn Myelle Farias Moreira; Yury Souza de Azevedo; Emilly Cassia Soares Furtado; Janielly Reis Castelhano; João Simão de Melo-Neto; Fabiana de Campos Gomes (Tropical Medicine and Infectious Disease)
Introduction: Human malaria is a zoonosis considered a serious global public health problem caused by five species of protozoa of the genus Plasmodium spp., which are transmitted by mosquito vectors belonging to the genus Anopheles spp. Objective: To verify whether there is a relationship between the age-standardized malaria mortality rate in Brazil and age–period–cohort effect variables, sociodemographic differences, and indicators of sustainable development. Methods: Data on malaria mortality in Brazil from 2000 to 2022 were analyzed using sociodemographic factors such as ethnicity, region of residence, and sustainable development indicators. Results: Statistical data demonstrated that from 2000 to 2022, there was a reduction in malaria mortality; the 0–4 years age group was more susceptible to death, and the infection affected more men, Indigenous people, and residents of the North Region. Environmental factors such as CO2 emissions and sanitation predict mortality in specific regions. The North and Northeast Regions had higher mortality rates. In the North, low CO2 emissions, deforestation, weak urban sanitation, a lower GDP, and a higher Gini index were related to high mortality; the latter was also a factor in high rates of deforestation and solid waste collection in the Central West and Northeast Regions. The number of consultations and professionals was a predictive factor for high rates in the three regions mentioned. The Southeast Region had the lowest mortality rate and lowest health expenditure, while the Northeast and Midwest Regions had the highest expenditure in this sector. Conclusions: This study can contribute to the direction of public policy due to the specificities of each region in Brazil.